Towards a Solution to the Goose-Agriculture Conflict in North Norway, 1988–2012: The Interplay between Policy, Stakeholder Influence and Goose Population Dynamics - Tombre, Ingunn; Eythórsson, Einar; Madsen, Jesper (PLoS ONE, 2013)
This paper presents results from a multidisciplinary study of a negotiation process between farmers and wildlife authorities which led to an agricultural subsidy scheme to alleviate conflicts between agriculture and geese in Norway. The Svalbardbreeding population of pink-footed geese Anser brachyrhynchus has increased considerably over the last decades and conflicts with farmers have escalated, especially at stopover sites in spring when geese feed on newly sprouted pasture grass. In Vestera°len, an important stopover site for geese in North Norway, farmers deployed scaring of geese at varying intensity dependent on the level of conflict during 1988–2012. We assessed the efficiency of a subsidy scheme established in 2006, in terms of its conflict mitigation, reflected in a near discontinuation of scaring activities. The presence of pinkfooted geese was analysed in relation to scaring intensity, the total goose population size and the increasing occurrence of another goose species, the barnacle goose Branta leucopsis. Scaring significantly affected the number of geese staging in Vestera°len, both in absolute and relative terms (controlling for total population size). The geese responded immediately to an increased, and reduced, level of scaring. Despite the establishment of the subsidy scheme, the number of pink-footed geese has recently declined which is probably caused by the increasing number of barnacle geese. For the farmers, the subsidy scheme provides funding that reduces the economic costs caused by the geese. Sustaining a low level of conflict will require close monitoring, dialogue and adaptation of the subsidy scheme to cater for changes in goose population dynamics. publishedVersion